Electrochemical and corrosion study of as-cast NixAly intermetallic alloys: Influence of alloy composition and electrolyte pH - Sefer, Birhan; Virtanen, Sannakaisa (Corrosion Science, 2019)
Electrochemical and corrosion behaviour of as-cast NixAly intermetallic alloys (Ni25Al75, Ni40Al60, Ni50Al50 and Ni75Al25 in at. %) is investigated and compared with commercially pure extruded/tempered Al and wrought Ni in pH 2, 6 and 12 buffered solutions. Different microstructures among the NixAly alloys are obtained, from single- to multi-phase systems. The electrochemical and corrosion behaviour of the NixAly intermetallic alloys is complex and depends on the Ni/Al-ratio, the microstructure, the pH value of the solution, and the passivation tendency. Three corrosion types are found to be operating, uniform corrosion, localised/pitting corrosion and intergranular corrosion, with pitting corrosion being the dominating type.
CRIS-Team WoS Importer:2019-04-04